On the Occurrence of Warty Structures in Rattan - Xu, J.; Liese, W.
A study on cellular details of rattan stems by the resin casting method revealed the presence of wart-like structures as apposition on the cell wallofmetaxylemvessels.protoxylemtracheids,fibresandalsoparenchyma. They were apparent for some species, but not observed in others. Conventional SEM confirmed the presence of warts with a considerable variation in occurrence. Therefore they have only limited taxonomic significance for the rattans.
Keywords: WARTS; RATTAN; WOOD ANATOMY; RESIN CASTING METHOD; SCAN NING ELECTRON MICROSCOPY